Identification of Secondary Metabolites and Proximate Analysis of Golden Apple Snails (Pomacea canaliculata L.) Meat Extract - Pertiwi, Meilisha Putri; Saputri, Dina Dyah (Jurnal ILMU DASAR, 2021)
The growth of golden apple snails is very rapid and causes losses of paddy production. Therefore snails are also called pest, especially agricultural pest. Control of golden apple snails can be done by physical hand sorting and then processed into animal feed. Based on research golden apple snails proven have good nutritional content. Efforts to use golden apples nails pets become useful things such as animal feed is a sustainable conservation. Therefore, this study aims to carry out secondary metabolites identification, proximate testing, and antioxidant content of golden apple snails as an initial reference for the basic ingredients of animal feed manufacturing. The method use is hand sorting of golden apple snails at the research location, then brought to the laboratory to carry out the process of secondary metabolites identification, proximate testing, and antioxidant analysis. The results showed a golden apple snails (Pomacea canaliculata L.) extract containing active compunds of alkaloids, flavonoids, tannins and polyphenols, steroids, and glycoside. Proximate analysis showed that golden apple snails extract had a high protein content of 40,83% compared to carbohydrates and fats. These findings suggested that golden apple snailsmeat extract has the potential to be further utilized as an alternative feed for Pangasius sp.Keywords: golden apple snails. Pangasius sp., proximate testing, secondary metabolites.